Multi-failure analysis of Seyhan dam and Çatalan dam - Kaya, Can. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Flooding risk due to a dam break has always been taken into consideration for the risk evaluation studies because of its serious potential damages to community and property located at downstream of the dam. In the scope of this thesis, the multi-failure dam break analysis of Seyhan Dam and Çatalan Dam has been carried out. The failures of the dams are not analyzed in terms of structural limits but it is assumed that the failure scenarios are based on some certain critical criteria that are exceeded. Because of their close proximity to Adana City, which is one of the most crowded cities in Turkey, Seyhan Dam and Çatalan dam have a key position to conduct this thesis work. The main goal of this study is to forecast the flood and its impacts due to multiple dam failures of Seyhan Dam and Çatalan Dam under specified circumstances and dam failure scenarios within the HEC-RAS computer software analysis program. Another objective of this study is to determine the inundated areas and the flood features affect the corresponding regions. Based on the flood routing analysis results and evaluations, the recommendations are presented in order to implement them to the areas under risk.
Keywords: Seyhan Dam (Turkey).; Çatalan Dam (Turkey).